KONTRIBUSI USAHA PENGUMPULAN LIMBAH PENAMBANGAN BATUBARA BAGI PENGHASILAN RUMAH TANGGA NELAYAN (Kasus Nelayan di Kelurahan Pasar Bengkulu, Kota Bengkulu) - Ramli, M; Khairunnisa, Khairunnisa (Jurnal Perikanan dan Kelautan, 2013)
Later fishing village Bengkulu Bengkulu City Market preoccupied with collectingwaste (residual leaching) of coal waste in the river Bengkulu. The waste collection bringadditional income for the families of fishermen who collect it. This study aims todetermine how many additional (contributed) coal waste collection for the familyincome of fishermen. Based on the results of the study contribute to the waste collectionfishermen families are quite large, reaching 41.91 % of total family income. Justunfortunately not all of the fishing village of Bengkulu market perform these activities,although they are a lot of free time, not a good time and the time after return to sea tosea. It is recommended to fishermen who have a lot of spare time to use it do extraefforts producer, for example coal waste collection (residual leaching) of coal miners .